1990
DOI: 10.1002/clc.4960130911
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic peptide response to ionic and nonionic contrast left ventriculography

Abstract: Summary:Atrial natriuretic peptide (ANP) levels were measured prior to and at 1 and 5 minutes postcontrast left ventriculography with an ionic contrast agent (diatrizoate), and a nonionic agent (iopamidol) and the results were compared. Since ionic contrast agents have been found to cause an increase in left ventricular end-diastolic pressure (LVEDP) and nonionic agents have been found to have less of an effect on LVEDP, we investigated the response of ANP levels, which have been found to increase secondary to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…MPAOP reflects left atrial pressure as well as left ventricular end diastolic pressure which has been shown to increase after left ventriculography with high and low osmolar CM (12,32). These haemodynamic changes correspond well with expansion of the intravascular volume and dilatation of the peripheral resistance vessels, thus increasing the pre-load.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…MPAOP reflects left atrial pressure as well as left ventricular end diastolic pressure which has been shown to increase after left ventriculography with high and low osmolar CM (12,32). These haemodynamic changes correspond well with expansion of the intravascular volume and dilatation of the peripheral resistance vessels, thus increasing the pre-load.…”
Section: Discussionmentioning
confidence: 92%
“…ANP is a circulating hormone deeply involved in the haemodynamic response to acute and chronic volume expansion (32,38). The hormone is mainly stored in the myocytes in the wall of the right atrium.…”
Section: Discussionmentioning
confidence: 99%